Exploring the efficacy of novel environmental stimuli to improve cardiorespiratory fitness and muscle health in older adults - Sian, Tanvir S. (2021)
The UK population is increasing, and people are living longer than ever before, which has implications for the whole of society. Increasing rates of comorbidity and ill-health associated with age is, and will continue to have, significant socioeconomic consequences when considering the treatment of chronic disease and comorbidity, and their implications for hospitalisation and social care for the older adult. The benefits of regular exercise for older adults have been extensively studied and are known to protect against and even reverse the effects of comorbidity. However, rates of exercise uptake amongst older but also younger adults are poor, with a worrying shift to more sedentary lifestyles in an increasingly technological age. The ageing population has also resulted in a generation of comorbid older adults for whom exercise is not possible and as such are prone to muscle wasting. In addition, low cardiorespiratory fitness, which results from prolonged inactivity, is also a risk factor for many cardiovascular and cardiometabolic diseases, and even premature mortality.